Exploring Gender-Dependent Relationships between Mobile Phone Screen Addiction and Sleep Quality - Princes, Elfindah; Erlis, Erlis (Journal of Business, Management, and Social Studies, 2023)
This research’s main purpose is to assess whether smartphone addiction have a significant effect on sleep quality moderated by gender. The respondents in this study were specifically young adults, and a quantitative methodology was employed. Questionnaires were distributed to participants, and the researchers used the responses to compile quantitative data. Like the preceding example, the survey conducted through purposeful sampling would be classified as quantitative due to its use of closed-ended questions with multiple choice responses on a 5-point Likert scale. The results of the study show that although gender is not a significant moderating influence, smartphone addiction does have an effect on sleep quality. The research presents novel managerial strategies, including the creation of technology-free zones for designated periods of time and the encouragement of a work environment that places a high value on work-life balance. These useful recommendations do more than just identify the issue; they also include doable solutions that may be applied in a variety of work environments.